Effect of Coating Materials and Storage Temperatures on Quality and Shelf Life of Papaya Fruit - Bambang S. Purwoko; P. Fitradesi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The objective of the research was to determine the effect of coating materials and storage temperatures in inhibiting the ripening process of papaya fruits. A two-factor factorial experiment was conducted. Replicates were three times and functioned as block. It consisted of coating material factor i.e. control, Semperfresh0 ,8% carnauba wax 6% and bee wax 6% and storage temperature factor, control room (27-31°C) and cool (18-20"C) temperatures. Observations consisted of weight loss, peel color development, appearance, total soluble solids, titratable acidity and vitamin C content. Result of the experiment showed that bee wax and carnauba wax inhibited weight loss, fruit softening, the increase of vitamin C, and the decline of appearance. Storage of fruits treated with carnauba wax at cool temperature had a shelf life of 19 days while control fruits stored at room temperature had a shelf life of 5.3 days. Keywords: Coating materials, Shelf life, Papaya